Інтертекстуальність у хореографічній лексиці та танцювальних практиках сучасного хореографічного мистецтва - Шевцова Ірина; Shevtsova Iryna; Продан Марина; Prodan Maryna (Видавництво «Код», 2025)
Резюме. Вивчення взаємозв’язків між текстами у танцювальних практиках дозволяє глибше зрозуміти механізми формування хореографічної мови, принципи композиційного та смислового конструювання танцювальних номерів, а також способи передачі художніх ідей через тіло та рух. Крім того, у контексті глобалізації мистецтва та інтенсивного культурного обміну інтертекстуальні зв’язки стають не лише засобом художньої виразності, а й способом включення локальних та традиційних танцювальних форм у сучасні практики, забезпечуючи їхню актуальність і впізнаваність. Дослідження інтертекстуальності в хореографії дозволяє створити цілісну наукову картину того, як танець функціонує як текст, як він взаємодіє з іншими мистецькими формами, і яким чином ця взаємодія збагачує художню практику, сприяє розвитку креативності та відкриває нові горизонти для міждисциплінарних досліджень у сфері мистецтва.

Abstract. Studying the interrelationships between texts in dance allows us to gain a deeper understanding of the formation of choreographic language, the compositional and semantic construction of dance pieces, and the ways in which artistic ideas are conveyed through movement and the body. In the context of the globalisation of art and intensive cultural exchange, intertextual connections are not only a means of artistic expression, but also a way of incorporating local and traditional dance forms into contemporary practices. This ensures the continued relevance and recognition of these forms. Studying intertextuality in choreography provides a comprehensive scientific understanding of how dance functions as a text, how it interacts with other art forms and how this interaction can enrich artistic practice, promote creativity and open up new avenues for interdisciplinary research in the arts. The analysis shows that intertextuality and intermediality are not just stylistic techniques, but «universal strategies of musical-semiotic thought», which are fully realized in choreographic art. Thanks to these concepts, choreography overcomes the limitations of the non-verbal medium, turning into an open system capable of conducting a dialogue with other works, types of art and cultural layers. For the modern Ukrainian choreographic school, intertextuality is of particular importance. This is not just a fashion trend, but a vital mechanism for dialogue with the national heritage and the world cultural context. By turning to literary sources, folk stage forms, and classical ballet plots, Ukrainian choreographers not only preserve but also actualize cultural memory, passing it on to new generations.
Intertextuality in the choreographic lexican and dance practices of contemporary choreographic art
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-15
Keywords: інтертекстуальність; хореографічна лексика; танцювальні практики; культурний концепт; міжтекстові зв’язки; композиційні структури; сучасне хореографічне мистецтво